Wood flame retardant and preparation method thereof, flame retardant OSB board and production method thereof
Through the composite wood flame retardant coated with ammonium sulfate and ammonium polyphosphate, the problems of darkening color, reduced mechanical properties and strong hygroscopicity caused by wood flame retardant are solved, and the moisture in the process is achieved Stable application in the environment, reduces the corrosion of exhaust gas treatment devices and extends the service life of the equipment.
Patent Information
- Application Number
- CN202310627068.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-05-30
AI Technical Summary
During the use of existing wood flame retardants, the color of the wood becomes darker, the mechanical properties are reduced, the reverse crystallization after hot pressing, and the hygroscopicity is strong, and the acid gas generated during the drying process damages the exhaust gas treatment device.
Aluminum hydroxide coated ammonium polyphosphate and silica coated ammonium sulfate as composite wood flame retardants, improve the loss resistance through different cladding materials, avoid yellowing and mechanical properties, and control the pH value to reduce Corrosiveness of exhaust gas treatment device.
It improves the loss resistance and mechanical properties of wood flame retardants, avoids darkening of the plate color and anti-crystallization, reduces hygroscopicity, is suitable for humid environments, and significantly extends the service life of the exhaust gas treatment device.
Smart Images

Figure CN116787567B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flame retardant board materials, and in particular, relates to a wood flame retardant and a preparation method thereof, and a flame retardant OSB board based thereon and a production method thereof. Background Art
[0002] As people's living standards improve, their requirements for living environment are getting higher and higher. Wood, as a natural organic material, is widely used in interior decoration, furniture manufacturing, house construction and other fields. However, as a flammable material, wood itself poses a huge hidden danger to people's property safety. Wood flame retardant is an additive that can improve the flame retardant properties of wood. However, the flame retardant effect of wood flame retardants currently on the market is average, and the pH value of the solvent is acidic, which corrodes wood processing equipment or metal parts such as light steel keels and screws during actual use.
[0003] There are many problems with the existing flame-retardant OSB on the market. For example, the color of the OSB board becomes darker after flame-retardant treatment, affecting the finishing effect of the substrate; the mechanical properties of the flame-retardant OSB are greatly reduced after flame-retardant treatment; the flame retardant is reverse-crystallized on the OSB board surface after hot pressing; the flame retardant has strong hygroscopicity, making the flame-retardant OSB unable to be used in humid environments.
[0004] At the same time, wood processing companies also need to face the task of exhaust gas treatment. Most wood flame retardants on the market produce strongly acidic gases during the drying process, which will greatly reduce the service life of the exhaust gas treatment device. This is also a major pain point in the development of flame-retardant OSB. Summary of the invention
[0005] The inventors of the present invention have found in their long-term research on the flame retardant properties of the boards that the main reasons for the various application problems of the above-mentioned OSB boards are: 1) The sulfate group in ammonium sulfate directly used as a flame retardant ingredient will promote the degradation of hemicellulose and lignin inside the wood, resulting in a yellowing reaction, which makes its color performance poor; 2) Ammonium polyphosphate and ammonium sulfate directly used as flame retardant ingredients, after being sprayed on the shavings, will experience anti-crystallization during the drying process, causing the adhesive to act directly on the crystals instead of the shavings, thereby affecting the bonding performance between the shavings, thereby reducing the mechanical properties.
[0006] To this end, the present invention provides a composite wood flame retardant, in which ammonium sulfate and ammonium polyphosphate are respectively coated with different coating materials, which can not only improve the anti-loss properties of the two, but also avoid the yellowing and mechanical property degradation caused by the above-mentioned direct application when used after coating.
[0007] The present invention specifically provides the following technical solutions:
[0008] A wood flame retardant, comprising the following components uniformly mixed with water as solvent:
[0009] Aluminum hydroxide coated ammonium polyphosphate, silicon dioxide coated ammonium sulfate, 1 to 10 parts of smoke suppressant, 1 to 15 parts of blending agent;
[0010] Among them, the aluminum hydroxide coated ammonium polyphosphate is a coated component formed by coating 40 to 55 parts of ammonium polyphosphate with 1 to 8 parts of nano-aluminum hydroxide and drying; the silicon dioxide coated ammonium sulfate is a liquid coated component formed by coating 20 to 40 parts of ammonium sulfate with 50 to 70 parts of silica sol;
[0011] All the above are parts by mass.
[0012] Furthermore, the degree of polymerization of the ammonium polyphosphate is at least 1000; and the particle size of the nano-aluminum hydroxide is 1000-1250 meshes.
[0013] Furthermore, the content of nano silicon dioxide in the silica sol is 20% to 40%.
[0014] Furthermore, the smoke suppressant is ammonium molybdate and / or zinc borate; and the blending agent is selected from at least one of dicyandiamide, melamine and boric acid.
[0015] Generally, the concentration of the wood flame retardant can be controlled to be 25wt% to 35wt%.
[0016] The present invention also provides a method for preparing the above-mentioned wood flame retardant, which comprises the following steps:
[0017] S1. Preparation of aluminum hydroxide-coated ammonium polyphosphate: 40-55 parts by weight of ammonium polyphosphate are added to anhydrous ethanol and fully dispersed to form a suspension, and then 1-8 parts by weight of nano-aluminum hydroxide is added thereto, fully stirred, and heated at 70°C to 95°C for 60min to 120min, and dried to obtain;
[0018] S2. Preparation of silica-coated ammonium sulfate: dissolve 20 to 40 parts by weight of ammonium sulfate in 50 to 70 parts by weight of silica sol, fully disperse and dissolve, and obtain the product;
[0019] S3. The aluminum hydroxide-coated ammonium polyphosphate obtained in step S1 and the silicon dioxide-coated ammonium sulfate obtained in step S2 are fully dissolved and dispersed in water with 1 to 10 parts by weight of a smoke suppressant and 1 to 15 parts by weight of a blending agent to obtain a wood flame retardant.
[0020] Generally, in step S1, 60 to 80 parts by mass of anhydrous ethanol can be used to disperse the ammonium polyphosphate, and the stirring speed can be controlled to 1000 rpm to 1500 rpm.
[0021] Generally, in step S2, stirring at a speed of about 500 rpm for about 30 minutes can achieve sufficient coating of ammonium sulfate by nano-silicon dioxide in the silica sol; of course, by appropriately increasing or decreasing the speed, the stirring time can be adjusted to be less or more to achieve a comparable coating effect.
[0022] The above-mentioned wood flame retardant provided by the present invention, first, the aluminum hydroxide coated ammonium polyphosphate is deposited on the surface of the ammonium polyphosphate by aluminum hydroxide, thereby reducing the hygroscopicity of the ammonium polyphosphate; due to the small particle size, easy adsorption, stable properties of aluminum hydroxide, and its own flame retardant and smoke suppression properties, it is very suitable for use as a polymer matrix coating for the flame retardant component ammonium polyphosphate, thereby reducing the loss rate of the flame retardant component ammonium polyphosphate. Compared with the ammonium polyphosphate coated with other materials such as epoxy resin on the market, due to the flammability of the epoxy resin itself and the large amount of toxic smoke generated after combustion, it is not suitable as a wood flame retardant. Secondly, the silica-coated ammonium sulfate is formed by ammonium sulfate being wrapped by nano-silica in neutral silica sol, so that it does not come into contact with alkaline reagents, and will not encounter alkali or heat during the production process to cause a large amount of ammonia gas to be emitted, affecting the flame retardant effect and workshop environment; and in the spraying process of its application, the shavings themselves can fully absorb the ammonium sulfate flame retardant solution, and the flame retardant component ammonium sulfate will not adhere to the surface of the shavings. After hot pressing, no crystals are precipitated on the surface of the slab, which will not cause the adhesive to act only on these crystals and be unable to bear force, thereby overcoming the problem that the slabs on the market are prone to anti-crystallization after hot pressing, and the flame retardant component ammonium sulfate has poor bonding with wood, thereby affecting the mechanical properties of the slabs.
[0023] At the same time, the above-mentioned wood flame retardant, based on the above-mentioned weakly acidic aluminum hydroxide-coated ammonium polyphosphate and silicon dioxide-coated ammonium sulfate, also has a smoke suppressant and a blending agent. On the one hand, the smoke suppressant and the aluminum hydroxide as a coating layer can not only improve the flame retardant effect, but also reduce the smoke production when it is used; on the other hand, the smoke suppressant and the blending agent ensure that the pH of the entire wood flame retardant is controlled between 7 and 8, and the pH of the steam collected after it is applied to the impregnated planing is only about 6, which greatly reduces the problem that most wood flame retardants on the market are acidic in themselves and cause the volatile gases to be too acidic (pH as low as 2 to 4) when encountering acidic wood, which is very corrosive to the exhaust gas treatment device, greatly reduces the service life of the exhaust gas treatment device, and causes a significant increase in production costs (such exhaust gas treatment devices are expensive).
[0024] Based on the above-mentioned wood flame retardant, the present invention also provides a flame-retardant OSB board, which is obtained by gluing, paving, hot pressing and trimming flame-retardant shavings; wherein the flame-retardant shavings are obtained by spraying the above-mentioned wood flame retardant on the shavings and drying them to a moisture content of 2% to 10%.
[0025] Generally, the length, width and thickness of the shavings are 5mm to 15mm, 1mm to 5mm and 0.2mm to 0.8mm.
[0026] Generally, the chips are pine chips, preferably chips obtained by rotary cutting on logs such as radiata pine.
[0027] The flame retardant OSB board is obtained by the following production method:
[0028] Q1, spray the wood flame retardant on the surface of the shavings, and dry them to a moisture content of 2% to 10% to obtain flame-retardant shavings;
[0029] Q2. Apply glue to the flame-retardant shavings and pave them to obtain slabs;
[0030] Q3. The slab is hot-pressed and trimmed to obtain a flame-retardant OSB board.
[0031] Further, in step Q1, the wood flame retardant is provided and sprayed according to a ratio in which the solid content of the flame retardant (i.e., the total mass of the four components of aluminum hydroxide-coated ammonium polyphosphate, silica-coated ammonium sulfate, smoke suppressant, and blending agent) is 8% to 12% of the dry weight of the chips.
[0032] In the above-mentioned production method, operations such as gluing, paving, hot pressing, trimming, etc. can follow the conventional processes of general OSB boards, and will not be described in detail here.
[0033] Generally, in step Q1, the drying temperature is generally controlled at 103°C to 120°C and the drying time is controlled at 30min to 40min, so that the moisture content can be reduced to the required range.
[0034] In step Q2, the adhesive used for gluing is selected from any one of MDI glue, urea-formaldehyde resin, and phenol-formaldehyde resin.
[0035] The surface-to-core ratio of the paving is 2.5-3:4-5:2.5-3.
[0036] Generally, in step Q3, the temperature of hot pressing is 160° C. to 185° C., the time is 2 min to 5 min, and the unit pressure is 2.5 MPa to 3.8 MPa.
[0037] The flame-retardant OSB board provided by the present invention, firstly, based on the characteristics of the aforementioned wood flame retardant, will not cause yellowing reaction between the flame retardant component and the internal components of the wood at high temperature during the conventional hot pressing process, and will not cause serious blackening of the board surface, so the obtained board has a good appearance. Secondly, based on the aforementioned neutral wood flame retardant, the obtained board is much less corrosive to metal parts commonly used in decoration, such as light steel keels and self-tapping screws, than the flame-retardant OSB boards commonly used in the market, and can also reduce after-sales problems between dealers and end customers. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a physical appearance diagram of a flame-retardant OSB board provided according to Application Example 1 of the present invention;
[0039] Figure 2 This is a physical appearance picture of a comparative OSB board made of a comparative flame retardant provided in Comparative Example 1 of the product of the present invention;
[0040] Figure 3 This is a physical appearance picture of a comparative OSB board made of a comparative flame retardant provided in product comparative example 2 of the present invention. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be described in detail below in conjunction with specific implementation methods, but the following embodiments are only specific elaborations of the technical solution of the present invention and are not intended to limit all of them. It is understood by those skilled in the art that conventional extensions in the art are made in accordance with the principles thereof and all belong to the protection scope of the present invention.
[0042] Product Example 1
[0043] This embodiment provides a wood flame retardant and a preparation method thereof.
[0044] First, 45 parts by mass of ammonium polyphosphate (with a degree of polymerization of about 1000) was added to 75 parts by mass of anhydrous ethanol and stirred thoroughly to form a suspension, and then 5 parts by mass of nano-aluminum hydroxide (with a particle size of 1000-1250 mesh) was added and stirred thoroughly and heated to 90°C and stirred (1000 rpm) for 60 min. After drying, aluminum hydroxide-coated ammonium polyphosphate was obtained.
[0045] Secondly, 30 parts by mass of ammonium sulfate was dissolved in 60 parts by mass of silica sol (wherein the content of nano-silicon dioxide was 30%), and stirred at 500 rpm for about 30 minutes until the mixture was evenly dispersed and completely dissolved, to obtain a silica-coated ammonium sulfate solution.
[0046] Next, the aluminum hydroxide-coated ammonium polyphosphate and the silicon dioxide-coated ammonium sulfate solution obtained above were dissolved in water with 5 parts by mass of ammonium molybdate and 10 parts by mass of dicyandiamide to prepare a wood flame retardant with a concentration of 30 wt%.
[0047] Product Example 2
[0048] The similarities between this product example and product example 1 are not described here, and only the differences from product example 1 are described. The difference between this product example and product example 1 is that the smoke suppressant used is zinc borate, the blending agent is a mixture of equal masses of boric acid and melamine, and the amount of water is adjusted; the rest is referred to as described in product example 1, and a wood flame retardant with a concentration of 35wt% is prepared.
[0049] Product Example 3
[0050] The similarities between this product embodiment and product embodiment 1 are not described here, and only the differences from product embodiment 1 are described. The difference between this product embodiment and product embodiment 1 is that: in the first step, the mass fractions of ammonium polyphosphate used are 40 parts, anhydrous ethanol is 65 parts, and nano aluminum hydroxide is 1 part; in the second step, the mass fractions of ammonium sulfate used are 20 parts, and silica sol is 50 parts (wherein the content of nano silicon dioxide is 40%); in the third step, 1 part of ammonium molybdate and 1 part of dicyandiamide are used, and the amount of water is adjusted; the rest is referred to as described in product embodiment 1, and a wood flame retardant with a concentration of 25wt% is prepared.
[0051] Product Example 4
[0052] The similarities between this product embodiment and product embodiment 1 are not described here, and only the differences from product embodiment 1 are described. The difference between this product embodiment and product embodiment 1 is that: in the first step, the mass fractions of ammonium polyphosphate used are 55 parts, anhydrous ethanol is 80 parts, and nano aluminum hydroxide is 8 parts; in the second step, the mass fractions of ammonium sulfate used are 40 parts, and silica sol is 70 parts (wherein the content of nano silicon dioxide is 20%); in the third step, 10 parts of ammonium molybdate and 15 parts of dicyandiamide are used, and the amount of water is adjusted; the rest is referred to as described in product embodiment 1, and a wood flame retardant with a concentration of 35wt% is prepared.
[0053] Application Example 1
[0054] This application example provides a flame-retardant OSB board and a method for making the same based on the wood flame retardant provided in product example 1.
[0055] First, large planing chips (length, width, and thickness of 5 mm to 15 mm, 1 mm to 5 mm, and 0.2 mm to 0.8 mm) planed from radiata pine logs were selected, and the wood flame retardant provided in Product Example 1 was evenly sprayed on the surface of the planing chips according to a solid content of 10% of the dry weight of the planing chips, and then placed in a drying oven and dried at 103° C. for about 40 minutes until the moisture content reached 2% to 10%, thereby obtaining flame-retardant planing chips.
[0056] Then, MDI glue was applied at a dosage of 3% and emulsified paraffin was applied at a dosage of 2%, and stirred at a rotation speed of 200 rpm for about 20 minutes. Directional paving was then performed at a surface-to-core ratio of 3:4:3 to obtain a slab.
[0057] Finally, the slab was hot pressed at a temperature of 180° C. and a pressure of 3.8 MPa for 2 min, and trimmed to obtain a flame-retardant OSB board.
[0058] Application Example 2
[0059] The similarities between this application example and application example 1 are not described here, and only the differences from application example 1 are described. The difference between this application example and application example 1 is that the wood flame retardant provided in the above product example 2 is used; the wood flame retardant provided in product example 2 is sprayed evenly on the surface of the shavings according to the solid content of which is 8% of the dry weight of the shavings, and then placed in a drying oven and dried at 120°C for about 30 minutes until the moisture content reaches 2% to 10%, thereby obtaining flame-retardant shavings.
[0060] Then, MDI glue was applied at a dosage of 3% and emulsified paraffin was applied at a dosage of 2%, and stirred at a rotation speed of 200 rpm for about 20 minutes. Directional paving was then performed at a surface-to-core ratio of 2.5:5:2.5 to obtain a slab.
[0061] Finally, the slab was hot pressed at a temperature of 160° C. and a pressure of 2.5 MPa for 5 min, and trimmed to obtain a flame-retardant OSB board.
[0062] The rest is as described in Application Example 1 to obtain a flame retardant OSB board.
[0063] Application Example 3
[0064] The similarities between this application example and application example 1 are not described here, and only the differences from application example 1 are described. The difference between this application example and application example 1 is that the wood flame retardant provided in the above-mentioned product example 3 is used; the wood flame retardant provided in product example 3 is sprayed evenly on the surface of the shavings according to the solid content of which is 12% of the dry weight of the shavings, and then placed in a drying oven and dried at 110°C for about 35 minutes until the moisture content reaches 2% to 10%, thereby obtaining flame-retardant shavings.
[0065] Then, MDI glue was applied at a dosage of 3% and emulsified paraffin was applied at a dosage of 2%, and stirred at a rotation speed of 200 rpm for about 20 minutes. Directional paving was then performed at a surface-to-core ratio of 3:4:3 to obtain a slab.
[0066] Finally, the slab was hot pressed at a temperature of 170° C. and a pressure of 3 MPa for 4 min, and trimmed to obtain a flame-retardant OSB board.
[0067] The rest is as described in Application Example 1 to obtain a flame retardant OSB board.
[0068] Application Example 4
[0069] The similarities between this application example and application example 1 are not described here, and only the differences from application example 1 are described. The difference between this application example and application example 1 is that the wood flame retardant provided in the above product example 4 is sprayed uniformly on the surface of the shavings according to the solid content of 10% of the dry weight of the shavings; the rest is as described in application example 1, and a flame-retardant OSB board is obtained.
[0070] In order to demonstrate the effects of the above-mentioned wood flame retardants provided by the present invention, the following comparative experiments were conducted. In the following comparative experiments, a variety of product comparison examples were provided.
[0071] Product Comparative Example 1
[0072] The comparative example of this product provides a conventional soluble wood flame retardant on the market as a comparison, which is specifically the No. 8126 wood flame retardant of Wanhua Chemical Group Co., Ltd., and a flame retardant solution with a concentration of 30wt% is prepared.
[0073] Product Comparative Example 2
[0074] This product comparative example provides a conventional insoluble wood flame retardant on the market as a comparison, which is specifically the HT-105 inorganic flame retardant produced by Shandong Taixing New Materials Co., Ltd., and a flame retardant slurry with a concentration of 30wt% is prepared.
[0075] Product Comparative Example 3
[0076] The comparative example of this product refers to the technical solution in the prior art CN 114315225A, and provides a wood flame retardant in which ammonium polyphosphate is double-coated with aluminum hydroxide and dopamine.
[0077] Among them, referring to the first step in product example 1, after preparing the aluminum hydroxide-coated ammonium polyphosphate, it was added to a 2g / L dopamine solution, fully stirred at room temperature for coating, and filtered, washed, and dried to obtain a dopamine-aluminum hydroxide double-coated ammonium polyphosphate microcapsule flame retardant.
[0078] Product Comparative Example 4
[0079] This product comparative example refers to the technical solution in the prior art CN 103056941A, and provides a comparative wood flame retardant in which the main flame retardant components are all coated with silicon dioxide. It is specifically prepared by the following method:
[0080] 300g of ammonium sulfate, 300g of monoammonium phosphate, 1000g of ammonium polyphosphate, 200g of aluminum hydroxide, 560g of zinc borate, 30g of silicon dioxide, and 2g of sodium dodecyl sulfate were added to 2200g of methanol under stirring at room temperature and dispersed evenly; then 200g of silica sol with a silicon dioxide content of 30% and a pH value of 9.0 was added to the dispersion, stirred at room temperature for 50min, and then filtered and dried to obtain a comparative wood flame retardant.
[0081] Product Comparative Example 5
[0082] This product comparison ratio is intended to reflect the effect of the blending agent on the performance of the final wood flame retardant.
[0083] The similarities between this product comparative example and product example 1 are not described here, and only the differences from product example 1 are described. The difference between this product comparative example and product example 1 is that in the third step, aluminum hydroxide-coated ammonium polyphosphate, silicon dioxide-coated ammonium sulfate solution and ammonium molybdate are dissolved in water to prepare a comparative wood flame retardant with a concentration of 30wt%.
[0084] Product Comparative Example 6
[0085] This product comparison is intended to highlight the impact of the coating correspondence on the performance of the final wood flame retardant.
[0086] The comparative wood flame retardant provided in this product comparative example is specifically prepared by the following method:
[0087] Ammonium polyphosphate and ammonium sulfate were added into anhydrous ethanol and stirred thoroughly to form a suspension, and then nano-aluminum hydroxide was added, stirred thoroughly and heated at the same time, and then dried to obtain a comparative wood flame retardant.
[0088] The dosage of each component is consistent with that in product example 1.
[0089] Product Comparative Example 7
[0090] This product comparison is intended to highlight the impact of the coating correspondence on the performance of the final wood flame retardant.
[0091] The comparative wood flame retardant provided in this product comparative example is specifically prepared by the following method:
[0092] Dissolve ammonium polyphosphate and ammonium sulfate in silica sol and stir and disperse them evenly until they are completely dissolved to obtain a modified flame retardant mixture.
[0093] The dosage of each component is consistent with that in product example 1.
[0094] The pH values of various wood flame retardants provided in the above product examples and product comparison examples were tested, as shown in Table 1 below.
[0095] Table 1 pH values of various wood flame retardants provided in product examples and product comparison examples
[0096]
[0097] It can be seen from Table 1 above that the pH of the commonly used soluble wood flame retardant solution on the market provided in Product Comparative Example 1 is strongly acidic, the pH of the commonly used insoluble wood flame retardant on the market provided in Product Comparative Example 2 is strongly alkaline, and the pH of the wood flame retardant solution provided by Product Examples 1 to 3 of the present invention tends to be neutral. It can be seen from Product Comparative Example 5 that the comparative flame retardant solution obtained without adding a conditioning agent is acidic. In contrast, the conditioning agent of the present invention is an alkaline substance, and the pH value of the flame retardant solution obtained by adjusting the flame retardant is slightly alkaline without affecting the flame retardant properties of the flame retardant. It is known that the optimal working environment of industrial tail gas treatment equipment is pH 6 to 8. From the pH values of each flame retardant in Product Examples 1 to 3 and Product Comparative Examples 1, 2, and 5 in Table 1 above, it can be seen that the pH value of the flame retardant solution directly affects the service life of the equipment.
[0098] The same preparation method as in Application Example 1 was adopted to prepare comparative OSB boards using the various wood flame retardants provided in the above product comparative examples.
[0099] Take the actual photos of the flame-retardant OSB board provided in the above-mentioned application example 1 and the comparative OSB board made of the comparative flame retardant provided in the product comparative examples 1 and 2, respectively. Figures 1 to 3 It should be noted that in order to fully demonstrate the effects of the various OSB boards obtained, Figures 1 to 3 It can only be presented in the form of the original physical image. After decolorization, it will be impossible to clearly distinguish the physical effects of each board.
[0100] Comparison Figure 1 According to the flame-retardant OSB board of Application Example 1 of the present invention, the comparative OSB board ( Figure 2 ), serious blackening of the board surface occurs, which is caused by the degradation of sulfate ions in conventional commercially available flame retardants with hemicellulose and lignin at high temperatures, and sulfate ions promote the yellowing reaction of wood; while the flame-retardant OSB board in Example 1 uses the wood flame retardant in Product Example 1, in which ammonium sulfate is fully coated, so the ammonium sulfate is stable during the hot pressing process and does not form free sulfate ions.
[0101] Comparison Figure 1 According to the flame-retardant OSB board of Application Example 1 of the present invention, the comparative OSB board ( Figure 3 ), since the insoluble flame retardant cannot be fully absorbed by the wood, a large amount of white area, namely flame retardant powder, appears on the board surface after board making, thus affecting the surface effect of the board.
[0102] The single combustion performance of the flame-retardant OSB boards provided in each application example and the comparative OSB boards obtained corresponding to the above-mentioned product comparison examples was tested, and the results of various test indicators are shown in Table 2 below.
[0103] Table 2 Combustion performance of various flame-retardant OSB boards provided in the application examples and various comparative OSB boards
[0104]
[0105] According to the national standard GB 8624-2012, the performance indicators of B1B grade are burning rate growth index ≤120W / S, total heat release within 600s ≤7.5MJ, and flame lateral spread does not reach the edge; the performance indicators of B1C grade are burning rate growth index ≤250W / S, total heat release within 600s ≤15MJ, and flame lateral spread does not reach the edge.
[0106] In Table 2, from the flame-retardant OSB boards provided by application examples 1 to 4 of the present invention and the comparative OSB boards made of the comparative flame retardant provided by product comparison example 5, it can be seen that with the better flame retardant properties of the modified ammonium polyphosphate and ammonium sulfate, the board performance indicators can reach B1B level, and the test data also exceed the standard value by a large margin.
[0107] The comparative OSB boards made with the comparative flame retardants provided in product comparative examples 1 and 2 only meet the B1C flame retardant standard, while the comparative OSB boards made with the comparative flame retardants provided in product comparative examples 3 to 7 only meet the B1C standard, and their performance is not stable enough, and there is a possibility that the performance of the finished products will not meet the standards after mass production conversion.
[0108] The comparative OSB board made of the comparative flame retardant provided in product comparative example 3 has poor affinity with wood in the solution due to secondary coating, and cannot be fully absorbed by wood. Some flame retardants naturally fall off on the surface of the planing during the production and processing, so the flame retardant performance is poor. At the same time, because most woods are acidic in nature, dopamine, which is the material of the outermost coating layer, will be protonated in an acidic environment, that is, after combining with wood, it is very easy to volatilize into the air during the drying process. Dopamine will affect people's emotions after being inhaled by the human body, giving people a good feeling. Long-term inhalation will make people addicted. After leaving dopamine, people often lose their appetite and become listless, which will have certain negative effects on the human body.
[0109] From the comparative OSB board made of the comparative flame retardant provided in product comparative example 4, it can be seen that the medium-strong alkali of ammonium sulfate undergoes an acid-base reaction inside the silica sol solution to generate ammonia gas, and the silica sol coating of various substances will affect the coating effect of the ammonium sulfate monomer, resulting in some ammonium sulfate being unable to be coated. During the hot pressing process of the board, the ammonium ions in the ammonium sulfate will decompose into ammonia gas and be lost. The reduction in the nitrogen content of the flame retardant will directly affect the flame retardant properties of the board, resulting in a decrease in the flame retardant properties of the flame retardant.
[0110] It can be seen from the comparative OSB boards made of the comparative flame retardants provided in product comparison examples 6 and 7 that the flame retardant performance is poor. This is because aluminum hydroxide cannot coat ammonium sulfate and silica sol cannot coat ammonium polyphosphate, and the loss of flame retardants leads to a decrease in flame retardant performance.
[0111] Specifically, for the comparative flame retardant provided in product comparative example 6, the ultrafine aluminum hydroxide forms a colloid when mixed with water due to its larger specific surface area and higher surface energy. The colloid is charged and can adsorb light and small substances. The solubility of ammonium polyphosphate with a degree of polymerization of more than 1000 in water is small. At this time, the ultrafine aluminum hydroxide can have a good coating effect on the ammonium polyphosphate product. For other substances such as ammonium sulfate and diammonium phosphate flame retardants, due to the large solubility of ammonium sulfate in water, light and small substances cannot be formed in the solution, so electrostatic adsorption cannot be generated, and therefore, it cannot be used as a carrier for aluminum hydroxide coating.
[0112] As for the comparative flame retardant provided in Comparative Example 7, since the adsorption principle of silica sol is that under certain conditions, the silica sol reacts with the separated substance, and this reaction is mainly physical and chemical. The physical effect comes from the van der Waals force between the silica surface and the solute molecules, and the chemical effect is mainly the hydrogen bonding between the silanols on the silica surface and the substance to be separated. However, the silanols on the surface of the silica sol can produce hydrogen bonding with the ammonium ions in ammonium sulfate, thereby achieving the purpose of silica sol coating ammonium sulfate, while for other substances such as ammonium polyphosphate and other substances with a high degree of polymerization, due to their stable properties, they cannot form hydrogen bonding with the silanols and cannot form effective coating.
[0113] It is not difficult to see from the application effects of the comparative flame retardants provided by the comparative proportions of each product that flame retardant monomers such as ammonium polyphosphate and ammonium sulfate will be lost in a humid environment after the board is formed if they are not coated, and failure to fully coat will also lead to the loss of crystals and a decrease in nitrogen content, thereby affecting the flame retardant properties.
[0114] The physical and chemical properties of the flame-retardant OSB boards and the comparative OSB boards provided in the application examples were tested, and the results of the various test indicators are shown in Table 3 below.
[0115] Table 3 Physical and chemical properties of various flame retardant OSB boards provided in the application examples and various comparative OSB boards
[0116]
[0117] According to the group standard LYT 1580-2010 oriented strand board, it can be seen from the test results in Table 3 that the physical and chemical properties of the flame-retardant OSB boards provided in Examples 1 to 3 and the comparative OSB board made with the comparative flame retardant provided in Comparative Example 5 can all reach the OSB / 2 type standard.
[0118] The comparative OSB board made of the comparative flame retardant provided in product comparative example 1 cannot meet the standards for various physical and chemical properties because the commercially available soluble flame retardant is not easily absorbed by the wood and forms crystals on the wood surface, and the MDI glue cannot form overlaps between the woods.
[0119] In the comparative OSB board made with the comparative flame retardant provided in product comparative example 2, since the commercially available insoluble flame retardant adheres to the wood surface, the MDI glue cannot provide strength between the wood, resulting in various physical and chemical properties not meeting the standards.
[0120] In the comparative OSB board made with the comparative flame retardant provided in product comparative example 3, the secondary coated crystals cannot be absorbed by the wood, resulting in the flame retardant crystals adhering to the surface of the shavings, and causing the MDI glue to be unable to form overlaps between the shavings, resulting in various mechanical properties not meeting the standards.
[0121] In the comparative OSB board made of the comparative flame retardant provided in product comparative example 4, the ammonium sulfate was not fully coated, and the ammonium sulfate itself absorbs water, so its 24h water absorption thickness standard cannot be met.
[0122] In the comparative OSB boards made with the comparative flame retardants provided in product comparison examples 6 and 7, the 24h water absorption thickness and internal bonding strength do not meet the standards. This is because aluminum hydroxide cannot coat ammonium sulfate and silica sol cannot coat ammonium polyphosphate. The water absorption and crystallization of the flame retardant affect the overlap between the MDI glue and the shavings, thereby resulting in performance degradation.
[0123] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A wood flame retardant, characterized in that: It comprises the following components which are mixed uniformly with water as solvent: Aluminum hydroxide coated ammonium polyphosphate, silicon dioxide coated ammonium sulfate, 1 to 10 parts of smoke suppressant, 1 to 15 parts of blending agent; The aluminum hydroxide coated ammonium polyphosphate is a coated component formed by coating 40 to 55 parts of ammonium polyphosphate with 1 to 8 parts of nano-aluminum hydroxide and drying; the silicon dioxide coated ammonium sulfate is a liquid coated component formed by coating 20 to 40 parts of ammonium sulfate with 50 to 70 parts of silica sol; the degree of polymerization of the ammonium polyphosphate is at least 1000; the particle size of the nano-aluminum hydroxide is 1000 to 1250 meshes; the content of nano-silicon dioxide in the silica sol is 20% to 40%; the smoke suppressant is ammonium molybdate and / or zinc borate; the conditioning agent is selected from at least one of dicyandiamide, melamine and boric acid; All the above are weight parts; The concentration of the wood flame retardant is 25 wt% to 35 wt%.
2. The method for preparing a wood flame retardant according to claim 1, characterized in that: Includes steps: S1. Preparation of aluminum hydroxide-coated ammonium polyphosphate: 40-55 parts by weight of ammonium polyphosphate are added to anhydrous ethanol and fully dispersed to form a suspension, and then 1-8 parts by weight of nano-aluminum hydroxide is added thereto, fully stirred, and heated at 70°C-95°C for 60min-120min, and dried to obtain; S2. Preparation of silica-coated ammonium sulfate: dissolve 20-40 parts by weight of ammonium sulfate in 50-70 parts by weight of silica sol, fully disperse and dissolve, and obtain the product; S3. Fully dissolve and disperse the aluminum hydroxide-coated ammonium polyphosphate obtained in step S1 and the silicon dioxide-coated ammonium sulfate obtained in step S2, 1 to 10 parts by mass of a smoke suppressant, and 1 to 15 parts by mass of a blending agent in water to obtain the wood flame retardant.
3. The preparation method according to claim 2, characterized in that: In step S1, 60 to 80 parts by mass of anhydrous ethanol are used to disperse the ammonium polyphosphate.
4. A flame retardant OSB board, characterized in that: The flame retardant shavings are obtained by gluing, paving, hot pressing and trimming; wherein the flame retardant shavings are obtained by spraying the shavings with the wood flame retardant according to claim 1 and drying them to a moisture content of 2% to 10%.
5. The method for manufacturing a flame retardant OSB board according to claim 4, characterized in that: Includes steps: Q1. Spray the wood flame retardant according to claim 1 onto the surface of the shavings, and dry them to a moisture content of 2% to 10% to obtain flame-retardant shavings; Q2, applying glue to the flame-retardant shavings and paving them to obtain a slab; Q3. The slab is hot-pressed and trimmed to obtain the flame-retardant OSB board.
6. The method according to claim 5, characterized in that: In step Q1, the wood flame retardant is sprayed onto the surface of the chips in an amount such that the solid content of the wood flame retardant is 8% to 12% of the dry weight of the chips.
